Diel and seasonal rhythms of asp Leuciscus aspius (L.) in a riverine environment. Issue 5 (3rd September 2017) - Horký, Pavel; Slavík, Ondrej
Abstract : A telemetry study analysing the diel and seasonal behaviour of asp was performed weekly in the Elbe River, Czech Republic, over 12 months. Asp diel movements and home range size varied across seasons, reaching maxima in summer and autumn with diurnal and/or crepuscular peaks of activity. On the contrary, no peaks of activity occurred during spring and winter, when the diel movements were low and the home range was small. Asp occurred predominantly within their home range. The probability of displaying migratory behaviour peaked during spring spawning and autumn wintering migrations (both triggered by temperatures from 4 to 8 °C). Three spawning grounds were detected within the studied river stretch. Most of the spawners utilised the first suitable spawning ground below the weir, which was not passed by any of the tagged specimens. Our results suggest a strong impact of weirs, even equipped with modern fish passes, on migratory behaviour and thus population dynamics of river-dwelling asp.